Volume interdiffusion coeffcient and uncertainty assessment for polycrystalline materials - Léchelle, Jacques; Noyau, S.; Aufore, Laurence; Arredondo, Antoine; Audubert, Fabienne (Diffusion Fundamentals, 2012)
A method has been developed in order to assess small volume interdiffusion coeffcients from experimental Electron Probe MicroAnalysis concentration profiles of polycrystalline materials by means of Boltzmann-Matano or den Broeder methods and their complementary Hall method. These methods have been used as tools for the investigation of the quasi-binary UO2/U(1-y)PuyO(2-z) interdiffusion, for which obtaining a solid solution in the bulk of grains is of major interest. In this paper uncertainties on the interdiffusion coefficient as a function of concentration have been computed for each method. Small volume cofficient measurements were enhanced by means of a small angle acquisition profile line with respect to the interdiffusion interface.